Kerklike gesag herbesoek: met verwysing na die kerklike proses om 'n belydenis of belydenisgrondslag te wysig - Celliers, A. (Acta theologica, 2016)
This article will show that the Christocratical understanding of church authority means that each of the official governing bodies of the church can make its own decisions based on the norm of the Word of God. This implies that the congregation or individual members of the congregation only have an advisory role in important church matters. This also means that synod and the General Synod cannot be held captive by lesser governing bodies. In any process in the Dutch Reformed Church to change Article 1 of their Church Order to include another Confession, for example the Belhar Confession, in their confessional base, this viewpoint on church authority should have an impact on the way in which church-governing bodies come to decisions on matters at hand. The civil court can revise decisions of church-governing bodies. Therefore, the church must confirm the correct formulation of relevant articles in the church order in order to ensure the Christological understanding of Church authority.